KOMPLEMENTER DAN REDUKSI KOMPETISI DALAM KETERKAITAN FUNGSIONAL DUA PUSAT RUANG PERKOTAAN DI KOTA JAYAPURA - Alfini Baharuddin; Bambang Hari Wibisono; Budi Prayitno; M Sani Roychansyah (Diponegoro University, 2017)
Jayapura City is the capital of Papua Province, located at the eastern end of Indonesia and has a direct borders with neighboring countries, Papua New Guinea (PNG). The geographical conditions of Jayapura City are very diverse leads to the formation of separate urban centers. Currently there are two parts of urban centers in Jayapura City, known as Jayapura and Abepura. This situation gave rise to a unique character in the overall system of Jayapura City, so it is necessary to examine how the two urban centers interact in Jayapura City. This study aims to assess the functional linkages that occur between Jayapura and Abepura using the case study method. Data collected through direct observation, secondary data collection and structured interviews using a questionnaire. The results showed that the functional linkages that occurred between Jayapura and Abepura are complementary functions of their natural advantages, and functions that are homogeneous but did not compete in the provision of economic and public service. In this case, the functions homogeneous appearing not cause competition, resulting in a reduction of competition.